Portas para o infinito: metafísica e misticismo em Bergson - Lima, Lucas de Moura (2019)
This paper intends to define what metaphysics, mysticism and morality are in Henri Bergson (1859-1941), mainly using the works Introduction to Metaphysics (1903) and The Two Sources of Morals and Religion (1932). Those are related concepts, and represent a thought´s progression through intuition´s levels. Metaphysics, science´s “sister”, would seek to apprehend the absolute. Mysticism would bring a complementary approach, in which the search for contact the deity would open a perspective for social transformation. Morality, which is divided into closed and open, would have in its open form a necessary counterpoint to mystical action. This is an misstudied Bergson´s aspect, but, through this work path, the understanding of this important philosopher may be expanded